Fish-based gelatin: exploring a sustainable and halal alternative - Reza, Muhammad; Annissa, Devi (Universitas Ahmad Dahlan, 2023)
Gelatin derived from fish has emerged as a promising alternative to traditional gelatin derived from mammals, primarily due to its potential to meet the rising demand for halal-certified products. This article provides a comprehensive overview of the utilization and extraction of gelatin derived from fish as a halal-compliant substitute. This study gathered information regarding the source, extraction method, and contribution to physicochemical properties and applications by reviewing the relevant literature. It discusses the most frequently consumed fish species, such as tilapia, mackerel, and catfish, which are halal and possess outstanding gel-forming properties. Type A gelatine (pre-treated acid) is distinguished from type B gelatine (pre-treated alkaline) based on the solvent used for pre-treatment. Seventy-five percent of the twenty gelatin extraction studies utilized alkaline pre-treatment (i.e., NaOH), where the base solution can eliminate non-collagen from the skin or bone of fish, thereby obtaining pure collagen. All extraction processes are conducted using the hot water extraction method at temperatures ranging from 45 to 70 °C. This method is time-efficient, accelerates collagen decomposition and gelatin solubility, and increases gelatin yield (from 5.33 to 68.75%). The effects of various procedures, including acid and alkaline extraction, on gelatin gel strength, moisture content, ash content, protein content, and fat content are investigated. According to SNI, gelatine has a gel strength between 50 and 300, a moisture content that does not exceed 16%, a lipid content that does not exceed 5%, and an average protein content that does not exceed 87.65%. However, ash concentrations typically persist above 3.25%, presumably due to using bases in pre-treatment processes that do not perfectly dissolve minerals compared to acids. In conclusion, the source and method of extraction will impact the gelatin's characteristics and applications. Keywords: Gelatin, Fish-based gelatin, Physicochemical properties, Traditional gelatin, SNI